2016
DOI: 10.1007/s00168-016-0797-y
|View full text |Cite
|
Sign up to set email alerts
|

Economic resilience in Great Britain: the crisis impact and its determining factors for local authority districts

Abstract: The 2008 recession has had a prolonged and varying effect both across and within countries. This paper studies the crisis impact on Great Britain's Local Authority Districts (LADs) using the concept of economic resilience. This country is an interesting case study as the impact varied significantly among LADs. The focus is on employment, and a new method is proposed for comparing pre-and post-recession conditions in order to assess the recession impact. The influence of a number of determining factors is exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
120
2
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(131 citation statements)
references
References 38 publications
4
120
2
5
Order By: Relevance
“…In our research, per capita GDP had negative effects on economic resistance during the global financial crisis. This result is in accordance with Lee's () findings where places with higher unemployment rates had a smaller crisis impact than places with lower rates, and Kitsos and Bishop () also found that regions in Great Britain with greater employment rates prior to the crisis exhibited the greatest employment losses in the subsequent period. Another interesting finding is that we found that both the proportion of employed persons in resource industries and the proportion of industrial output above the designated size in GDP had a negative impact on the economic resilience of RBCs.…”
Section: Conclusion and Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In our research, per capita GDP had negative effects on economic resistance during the global financial crisis. This result is in accordance with Lee's () findings where places with higher unemployment rates had a smaller crisis impact than places with lower rates, and Kitsos and Bishop () also found that regions in Great Britain with greater employment rates prior to the crisis exhibited the greatest employment losses in the subsequent period. Another interesting finding is that we found that both the proportion of employed persons in resource industries and the proportion of industrial output above the designated size in GDP had a negative impact on the economic resilience of RBCs.…”
Section: Conclusion and Discussionsupporting
confidence: 90%
“…Equilibrium approach considers resilience as a return to preexisting equilibrium point, namely engineering resilience or as a movement to a new state namely ecological resilience. (Kitsos & Bishop, 2018;Walker, Holling, Carpenter, & Kinzig, 2004). The evolutionary approach defined resilience as continuously adaptation to constantly changing conditions (Kitsos et al, 2018;Martin, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…• A large stock of human capital because of a relatively large subset of the population that is skilled, highly educated and entrepreneurial, will enable and drive renewal and adaptation (e.g. Giannakis & Bruggeman, 2017;Glaeser, 2005;Huggins & Thompson, 2015;Kitsos & Bishop, 2016).…”
Section: Labour Marketmentioning
confidence: 99%
“…Looking at the most downloaded papers, we see that the majority of the papers (3 out of 5) deals with the topic of resilience (Bristow and Healy 2018;Kitsos and Bishop 2018;Di Caro and Fratesi 2018). There are at least two explanations for this.…”
Section: Continued Broad Range Of Topics In Published Papersmentioning
confidence: 97%